Alcohol and tobacco induced infiltrating ductal carcinoma male: a case report - Yadav, Akhila Janga; Chowdary, Bhavana Pamulapati; Yadav, Divya Bharathi Jekkula; Penthala, Rajender; Bonkuri, Vineeth (International Journal of Research in Medical Sciences, 2019)
Male breast cancer is a rare cancer that forms in the breast tissue of men, it accounts for 1% of all the cancers in men. Recent epidemiological studies suggest that the incidence of MBC is increasing by 1.1% per year. Due to lack of knowledge and awareness, MBC cases are diagnosed lately, mostly during stages III /IV. Early detection and reduction of mortality and morbidity related to male breast cancer is essential. The present article provides a detailed study of a patient with Infiltrating ductal carcinoma, grade III with regional nodal metastasis and the patient is positive for both oestrogen and progesterone receptors. In this case the patient is alcoholic and had habit of chewing tobacco since childhood and one of the patient’s relative had female breast cancer. These are the probable risk factors in this particular case. The better knowledge regarding the male breast carcinoma can be obtained through the thorough study of the available male breast cases.